Pelatihan Pemanfaatan Google Maps dalam Promosi Destinasi Wisata: Mengangkat Potensi Padma Agrowisata dalam Meningkatkan Visibilitas Online Wisata Desa - Valentiana, Francisca; Fadhilah, Aisyah Zulfan; Syah, Moh. Handika Akbar; Putra, Haris Andhika; Fawa’id, Mohamad Wildan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to increase the online visibility of Padma Agrowisata, a village-owned enterprise (Bumdes) in Pandantoyo Village, Ngancar District, Kediri Regency, through training on the use of Google Maps in promoting tourist destinations. The service method used is participatory action research (PAR), which involves active participation from business owners, village governments, and the surrounding community. Through PAR, intensive training was carried out on how to utilize the Google Maps feature to increase Padma Agrowisata's exposure online. The result of this dedication is that Padma Agrowisata's visibility has significantly increased by making this tourist destination known to more people through online platforms. Thus, this service aims to support village economic growth by increasing the number of visitors and income from the tourism sector, as well as providing positive benefits for the local community.